(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Background: Sepsis during pregnancy, particularly in the context of fetal demise or invasive obstetric procedure, can progress rapidly to endotoxic shock and multi-organ failure, posing a significant threat to both maternal and fetal outcomes. This report presents a challenging case of a 27-years-old woman with a triplet pregnancy, conceived through in-vitro fertilization, who developed septicemia with endotoxic shock, disseminated intravascular coagulation (DIC), and multi-organ failure following fetal demise and fetoreduction. The case emphasizes the importance of a multidisciplinary approach in the critical care management of obstetric emergencies to maximize the maternal and fetal outcomes. Conclusion: This case underscores how sepsis and endotoxic shock should be considered as a top differential diagnosis in obstetric patients who come with circulatory collapse, fever, and organ failure. The mother recovered completely despite the initial life-threatening difficulties due to prompt identification of the infection (fetoreduction-associated septic focus), aggressive hemodynamic stabilization, and coordinated intensive care. Bangladesh J Obstet Gynaecol, 2025; Vol. 40(1): 43-46